2021
DOI: 10.1002/cti2.1266
|View full text |Cite
|
Sign up to set email alerts
|

Primary immunodeficiency‐related genes in neonatal intensive care unit patients with various genetic immune abnormalities: a multicentre study in China

Abstract: Objectives. The present phenotype-based disease classification causes ambiguity in diagnosing and determining timely, effective treatment options for primary immunodeficiency (PID). In this study, we aimed to examine the characteristics of early-onset PID and proposed a JAK-STATopathy subgroup based on their molecular defects. Methods. We reviewed 72 patients (< 100 days) retrospectively. These patients exhibited various immune-related phenotypes and received a definitive molecular diagnosis by nextgeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Diagnostic yield varies among reports, which is due to the difference in the characteristics of study populations and the methods used ( Supplementary Table S3 ). Previous studies used targeted panel sequencing ( 20 , 21 ), CES ( 22 ), whole exome sequencing (WES) ( 23 , 24 ), or whole genome sequencing ( 25 ), and each method has its pros and cons. With targeted gene panel sequencing, in-depth sequencing of selected genes related to IEI is possible, which enables detection of low-level mosaic variants, whereas with methods that can test a large number of genes, diagnostic yield would be increased.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic yield varies among reports, which is due to the difference in the characteristics of study populations and the methods used ( Supplementary Table S3 ). Previous studies used targeted panel sequencing ( 20 , 21 ), CES ( 22 ), whole exome sequencing (WES) ( 23 , 24 ), or whole genome sequencing ( 25 ), and each method has its pros and cons. With targeted gene panel sequencing, in-depth sequencing of selected genes related to IEI is possible, which enables detection of low-level mosaic variants, whereas with methods that can test a large number of genes, diagnostic yield would be increased.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 7 patients harbored mutations in 1 of the 4 genes (IL2RG, RAF1, IL10RA and HRAS), which could be mapped to the Janus kinase-signal transducer of activators of transcription pathway (hsa04630) and 5 of them was classified to PID (details in our previous study). 34 We observed that 5 genes (IL2RG, RAF1, IKBKG, FGFR2 and HRAS) were mapped to PI3K/Akt signaling pathway (hsa04151) and this pathway was shared by 3 PID patients and 4 non-PID ones. Recent studies [35][36][37] have begun to reveal a tightly-regulated system marked by extensive cross-talk among signaling pathways.…”
Section: Discussionmentioning
confidence: 87%
“…A total of 170 articles were included in the final review (alphabetically ordered based on author in Supplementary Table 2). 1,2,7–50,55,56,68–189 A PRISMA flow diagram is presented to track the process and number of studies included and excluded (Figure 1).…”
Section: Resultsmentioning
confidence: 99%